Chlorella and vegetable oil inclusion in diets for growing rabbits: effects on growth, digestibility, plasma metabolites, and caecal fermentations and microbiota - F. Bordignon; A. Trocino; P.J. Marín García; T. Larsen; G. Zardinoni; M. Molin; M. Birolo; P. Stevanato; G. Xiccato (Animal)
The inclusion of microalgae in livestock diets has been shown to enhance animal productivity, immune response, and meat quality. However, the role of chlorella (Chlorella vulgaris) in growing rabbit nutrition has been scarcely explored, with available studies focusing on low inclusion levels (<1%) and their effects on rabbit growth and immune response. This study evaluated the growth performance, nutrient digestibility, plasma metabolites, caecal fermentative activity, and caecal microbiota composition of growing rabbits fed diets with different inclusion levels of chlorella and crude fat. A total of 648 mixed-sex Grimaud crossbred rabbits (33 d of age; 841 ± 140 g live weight) were fed six experimental diets (96 rabbits per diet for the growth trial) based on a bifactorial design with three dietary inclusion levels of chlorella (0, 1, and 2%) and two levels of crude fat (3 and 5%) obtained by the inclusion of soybean oil (1 and 3%, respectively). The trial lasted 38 days until slaughter. From 47 to 51 days of age, 72 rabbits (12 per diet) were submitted to a digestibility trial. At 51 days of age, samples of plasma and caecal content were collected from 36 rabbits (six rabbits per diet) to analyse plasma metabolites, caecal fermentations, and caecal microbiota. Rabbit live weight at 71 days of age (2 700 g, on average), weight gain (48.8 g/d) and feed conversion ratio (3.27) were unaffected by chlorella inclusion, while feed conversion ratio improved (−5%; P < 0.001) with an increase of crude fat from 3 to 5%. The digestibility of ADF (23.2 vs 20.9%; P < 0.05) and crude fat (83.8 vs 85.6%; P < 0.01) improved with the inclusion of chlorella at 2%, as well as the digestibility of crude fat (82.4 vs 86.9%; P < 0.001) and gross energy (57.3 vs 58.7%; P < 0.001) with crude fat inclusion at 5%. Plasma non-esterified fatty acids decreased (−19%; P < 0.05) in diets with 5% crude fat. Neither chlorella nor crude fat inclusion levels affected other plasma metabolites, caecal fermentations, or caecal microbiota. Overall, the inclusion of chlorella up to 2% in diets for growing rabbits did not significantly affect diet nutritional value, animal performance, or caecal activity. On the other hand, increasing crude fat to 5% improved the overall feed efficiency.